Investigating the mediating role of maladaptive schemas and emotional expression in the relationship between childhood trauma and sexual intimacy in women from low-income families - Hadiyan, Nasim; Mottaghi, Shekoofeh; Rezapour Mirsaleh, Yasser (Applied Family Therapy Journal (AFTJ), 2023)
Purpose: The present study was conducted with the purpose of investigating the mediating role of maladaptive schemas and emotional expression in the relationship between childhood trauma and sexual intimacy in women from low-income families. Methods: This research was a descriptive-correlational research that was performed by structural equation modeling. The statistical population of the research included all women from low-income families under the coverage of Isfahan City Relief Committee, 209 of whom were selected by convenience sampling method and answered the questionnaires of sexual intimacy Batlani, Ahmadi and Bahrami (2010), Early maladaptive schemas Young (1994), Child Trauma Bernstein and Fink (1998), and Emotional Expressiveness of King & Emmones (1990). Research data were analyzed at two levels of descriptive and inferential statistics, especially structural equation modeling. Results: The findings showed that childhood trauma doesn’t significant effect on the sexual intimacy of married women in low-income families (P>0/05); but it has a significant effect on emotional expression and areas of early maladaptive schemas (P